Baclofen Toxicity in Children With Acute Kidney Injury: Case Reports and Review of the Literature - Mishaal, Ram A. (Child Neurol Open, 2020)
Baclofen is a medication used for tone management in cerebral palsy. Although it acts mainly at the spinal cord level, it can cause central nervous system adverse reactions at higher doses. Baclofen is mainly eliminated by renal excretion and there have been reports on adverse events when used in adults with renal impairment; however, there are no consensus guidelines as to the dose adjustments required due to renal impairment. The authors describe 2 children with acute kidney injury (AKI) and systemic side effects with initiation of oral baclofen, which was started for treatment of dystonia/spasticity in the recovery phase of their kidney injury. Following the initiation of the drug, they both had decreased level of consciousness and respiratory difficulties, which warranted discontinuation of the drug. These cases highlight the need for reduced initial dose, slow titration, and close monitoring when initiating baclofen treatment in children with AKI.